The effects of shear deformation in non-rectangular steel reinforced concrete structural walls - Luo, Da (2021)
Steel reinforced concrete composite (SRC) structural walls with embedded steel profiles have superb flexural strength and stiffness, which may lead to a more distinct influence on the shear deformation in these walls. If the walls have flanged sections, substantial influences of the shear lag effect could be expected. This paper investigates the portion of shear deformation and influences of the shear lag effect in non-rectangular composite structural wall with different design parameters by finite element method. Methods for calculating the portion of shear deformation and shear lag effect in design are proposed based on a truss analogy. The study shows that a large portion of shear deformation exists for steel-concrete composite walls, which could account for more than 40% of the total deformation while vertical strain of the steel profiles at end of the flange of SRC walls is significantly smaller than assumed by plane section assumption. These effects can be captured reasonably by the proposed methods.